The analysis of the stock of the Republican scientific-technical library - Alma Janulevičienė (Knygotyra)
Nowadays, the investigation of the questions of the scientific management of library stocks has gained great urgency (increased in importance). The tasks of increasing the efficiency of the formation and usage of library stocks highlight the necessity for systematic research into their peculiarities and tendencies of development.